Potencial zoonótico da microbiota fúngica de excretas de aves autóctones do cerrado e Pantanal matogrossense cativas no zoológico da Universidade Federal de Mato Grosso - Simi, Walquirya Borges (2013)
In the literature little has been reported about fungal microbiota in excreta of wild birds of the Pantanal and Cerrado. These birds are hosts of a rich fungal microbiota; assume an important role in the epidemiology of zoonoses including the opportunistic mycoses, which can cause serious health problems as a result. This was a cross-sectional descriptive study whose goal was the identification of fungi from the droppings of the birds of prey and psittacines located in 16 enclosures intended for visitation and three where animals remain in quarantine at the Zoo of UFMT. Therefore, excreta were collected from the following species of birds: Ema (Rhea americana), Maracanã Verdadeira (Primolius maracana), Arara Canindé (Ara ararauna) Red Macaw (Ara chloroptra), Blue Macaw (Anadorhynchus hyacinthinus), Araracanga (Ara macao), True Parrot (Amazona aestiva), Toco Toucan (Ramphastos toco), King Vulture (Sarcoramphus papa), Beautiful Hawk (Busarellus nigricollis), Tawny Owl (Bubo virginianus), Grey Eagle (Harpyaliaetus coronatus), Black Hawk (Urubutinga urubutinga), Duck Hawk (Spizaetus melanoleucos), Hawk plume (Spizaetus ornatus), Long-tailed (Buteo albonotatus) crochet lace and Real Hawk (Harpia harpyja). The methodology used was composed of collection of excreta in triplicate, dilution (1:30) in saline, isolation of colonies in Sabouraud dextrose agar plus chloramphenicol (120 mg/mL), and subsequent observation of macroscopic and micromorphological characteristics. In birds in enclosures (n= 60), A. niger was the fungal species most frequently isolated (41.1%) in Harpya harpyja and Candida kefyr (63.8 %) was the most frequent species in Ramphastos toco. Quarantine for birds (n= 40) were observed respectively equal to the percentage (76.6% - C. krusei) (84.4% - C. kefyr) and (15.2% - C. famata) considering Aratinga aurea, (76.2%- C. krusei) considering Amazona aestiva. These findings indicate the presence of potentially pathogenic species present in the excreta of the birds assessed and risk exposure of handlers and individuals that perform visitation to the Zoo. The birds of Cerrado and Pantanal matogrossense can act in epidemiological chain of major zoonoses.